Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2147/ott.s195853
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA FENDRR attenuates colon cancer progression by repression of SOX4 protein</p>

Abstract: Background and purpose: Homo sapiens FOXF1 adjacent noncoding developmental regulatory RNA (FENDRR) is a novel long noncoding RNA (lncRNA) exerting important effects on transcriptional and post-transcriptional regulation. The purpose of this study was to investigate the potential role of FENDRR in colon cancer. Methods: Multiple cellular and molecular biology experiments were performed in the present study, such as CCK-8, Western blot, immunohistochemistry, confocal immunoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Also, FENDRR was reported inhibiting various cancers such as colon cancer, hepatocellular carcinoma, etc. [13,19]. Similarly, FENDRR also had tumor suppressive property in CC, which was reflected by its downregulation in CC tissues and cells as well as the results of gain-of-function experiments.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Also, FENDRR was reported inhibiting various cancers such as colon cancer, hepatocellular carcinoma, etc. [13,19]. Similarly, FENDRR also had tumor suppressive property in CC, which was reflected by its downregulation in CC tissues and cells as well as the results of gain-of-function experiments.…”
Section: Discussionmentioning
confidence: 67%
“…However, biological effects and its mechanism with respect to CC remain to be explored. Mechanistically, FENDRR can exert tumor-inhibitory functions in colon cancer through repression of Sry-Related HMG-BOX-4 (SOX4) protein [13]. Moreover, FENDRR post-transcriptionally regulate Runt-related transcription factor 1 (RUNX1) by sponging miR-18a-5p [14].…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs), which are a recently discovered class of noncoding RNAs, are transcribed from noncoding sequences in the genome, are longer than 200 nt and do not have the ability to be translated into proteins (10,11). LncRNAs have become a novel research focus since numerous lncRNAs have been discovered that are closely related to the occurrence of a great number of diseases due to their extensive regulatory effects on epigenetics (12), transcription (13), and protein translation (14) and modification (15). Therefore, a systematic study of the regulatory role of lncRNAs in the pathogenesis of RA will help in more comprehensively understanding the mechanism of RA and providing new insight and targets for its clinical diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that the lncRNA HOTAIR promotes colon cancer development by downregulating miRNA-34a (Peng C. L. et al, 2019). The lncRNA FENDRR was found to inhibit colon cancer development by inhibiting the SOX4 protein (Liu and Du, 2019). In addition, a study found that the lncRNA CYTOR promotes metastasis in colon cancer through Wnt/βcatenin signaling (Yue et al, 2018).…”
Section: Introductionmentioning
confidence: 99%